Antimicrobial activity of acetic acid and colgate 360° antibacterial toothbrush®: an in vitro study - Herrera-Sandoval, Laura Viviana; Caballero-Romero, Stephanny Gissell; Claro-Numa, Andrea; Torres-Pinzón, Harold; Martínez-López, Carmen Alodia (Revista Facultad de Odontología Universidad de Antioquia, 2012)
Introduction: toothbrushes may become a potential source of oral pathogens when not properly disinfected once they have been used, especially in patients with infections of the stomatognathic system or among populations that do not often replace this instrument. The goal of this study was to compare the antimicrobial activity of 5% acetic acid with that of Colgate 360º antibacterial toothbrush® as possible strategies for toothbrush disinfection. Methods: this study included 48 toothbrush heads that were separately inoculated with Staphylococcus aureus, Streptococcus mutans and Cándida albicans. The heads were sorted out into three groups: heads treated with 5% acetic acid (white domestic vinegar, La Constancia®) for 10 minutes; 360º toothbrush heads with antibacterial properties, and control heads treated with saline solution. This was followed by calculations of CFU/ml of the microorganism remaining in the heads after treatment or time of action. Results: in presence of S. aureus, Colgate 360º antibacterial toothbrush® proved to have better antimicrobial activity than 5% acetic acid (PI:72.11 5). The two assessed treatments showed a similar capacity to eradicate S. mutans from the brush heads (p> 0,05); concerning C. albicans, the best antimicrobial activity was observed in the 5% acetic acid (PI: 99,9%). Conclusion: in vitro, both white domestic vinegar and Colgate 360º antibacterial toothbrush® remove microorganisms colonizing toothbrush heads, such as S. aureus, S. mutans y C. albicans, and are therefore considered good alternatives for keeping toothbrushes free of microoorganisms among several populations.